2018
DOI: 10.18517/ijaseit.8.2.4960
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Rehabilitation Exosceleton Movement Control using EMG Signal

Abstract: Post-stroke rehabilitation device is very important nowadays, considering the high rate of disability caused by stroke especially arm function. About 50% of stroke survivors experience the unilateral motor deficits which decreased upper extremity function. Therefore, hand and shoulders therapy are generally performed in advance to support patients' daily activities. Electromyograph (EMG) signals from selective muscles were proven to provide additional power for post-stroke rehabilitation device to recover more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Human participation in groups and organizations is called human resources. Human resources are seen as an important corporate asset, because human resources are dynamic and always needed in every process of producing goods and services [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Human participation in groups and organizations is called human resources. Human resources are seen as an important corporate asset, because human resources are dynamic and always needed in every process of producing goods and services [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Combining an Arduino Uno with an Olimex shield, working at 256 Hz sampling rate with a 10 bit ADC to detect and filter myoelectric signals, Rahmatillah et al developed an exoskeleton for both arms to support stroke patients during rehabilitation [ 110 ]. The authors suggested applying a Kalman filter to enable missing information from noisy indirect measurements, i.e., here to separate the myoelectric signals from noise and to smooth the signal for a better control of the motor at the rehabilitating arm.…”
Section: Emg Measurementsmentioning
confidence: 99%
“…As stated by previous researchers, bio-electrical signals or electromyography are influenced by muscle contractions in the related limbs [1]- [5] Whether or not the muscle contraction is normal is influenced by the functionality of the limbs, for example the upper limbs (hands and arms) or the lower limbs (legs). So for post-stroke patients who experience paralysis, it will indirectly affect the characteristics of muscle bioelectrical signals (EMG) both in amplitude and frequency [6]- [10].…”
Section: Introductionmentioning
confidence: 99%